Analisis Disiplin Kerja, Motivasi Kerja dan Pelatihan Terhadap Persepsi Kinerja - Prasetio, Chaidar Izet; Pragiwani, Meita; Prabantoro, Gatot (Jurnal Riset Manajemen dan Bisnis, 2024)
This study aims to determine and analyze the effect of work discipline on employee performance, determine and analyze the effect of motivation on employee performance, and determine and analyze the effect of training on employee performance at PT Satya Haprabu Perkasa. The strategy used in this study is an associative research strategy. While the research method used is a quantitative method. The data obtained are primary data from distributing questionnaires to respondents. The population of this study is all management and outsourcing at PT Satya Haprabu Perkasa totaling 137 people. The type of sampling chosen in this study is random sampling, using the slovin formula calculation, the number of samples in this study is 102 people. The data obtained is processed using SmartPLS 3.0. Statistical analysis of data in this study is descriptive data analysis, outer model analysis, inner model analysis and hypothesis testing. The results of this study indicate that there is an influence of work discipline variables on employee performance. There is an influence of work motivation variables on employee performance. There is an influence of training variables on employee performance at PT Satya Haprabu Perkasa.